PENEGAKAN PERATURAN DAERAH KABUPATEN BADUNG NOMOR 9 TAHUN 2010 TENTANG IZIN GANGGUAN - Kurniawan, Rikardus; R., Ibrahim; Dahana, Cokorda Dalem (Kertha Desa; Vol. 01, No. 01, Maret 2013)
in writing of this article have title is Enforcement of Badung Regency Regulation No. 9in 2010 On disorders permit. The problems have been arised in the enforcement of localregulation was the construction of tourism facilities such as hotels, villas, restaurants,entertainment venues and other places of business that do not have disorder permits.These type of study were empirical legal research. From the results of study have beenconducted at the Civil Service Police Unit of the Badung Regency the form of violationon local regulation of Badung regency No 9 in 2010 on disorder permit is theconstruction of places of business that do not have disorder permits. In the localregulation No 9 in 2010 on disorders permit of Badung regency government have beendetermined the legal consequences of administrative penalties and criminal penalties.In the enforcement of Badung regency regulation No. 9 in 2010 on disorder permit tobusiness places that do not have disorder permit from Badung regency governmenthave given administrative sanction in the form of closing the business places and thecompetent authority to impose sanctions in accordance with the decree of Badungregent No 12/03/HK/2012 is the regent cq Regulatory Enforcement Team of Badungregency.
Keywords: Enforcement, Local Regulation of Badung regency, Disorder Permit